1995
DOI: 10.2108/zsj.12.391
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C (PKC) Signal Transduction System Involved in Larval Metamorphosis of the Barnacle, Balanus amphitrite

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
1
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 13 publications
1
30
1
2
Order By: Relevance
“…Furthermore, our observations are also supported by some previous studies indicating that the reduction of NOS activity accelerated larval metamorphosis in the ascidian Ciona intestinalis (Comes et al, 2007) and the gastropod Crepidula fornicate (Pechenik et al, 2007). In contrast to previous findings regarding the role of PKC during B. amphitrite settlement (Yamamoto et al, 1995), we did not observe metamorphosis of any cyprid without attachment for all of NO level manipulations, suggesting NO signaling may control the overall settlement process in this species.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, our observations are also supported by some previous studies indicating that the reduction of NOS activity accelerated larval metamorphosis in the ascidian Ciona intestinalis (Comes et al, 2007) and the gastropod Crepidula fornicate (Pechenik et al, 2007). In contrast to previous findings regarding the role of PKC during B. amphitrite settlement (Yamamoto et al, 1995), we did not observe metamorphosis of any cyprid without attachment for all of NO level manipulations, suggesting NO signaling may control the overall settlement process in this species.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, the involvement of pheromones, hormones, neurotransmitters and proteins in regulating larval settlement of B. amphitrite has been intensively studied (e.g. Clare et al, 1995;Yamamoto et al, 1995;Yamamoto et al, 1997;Matsumura et al, 1998b;Matsumura et al, 1998c;Yamamoto et al, 1999;Delort et al, 2000;Endo et al, 2009;Gallus et al, 2010). Based on these results, it has been suggested that signaling transduction systems are likely involved in transmitting and/or translating these exogenous signals to endogenous effectors, resulting in the initiation of larval settlement (Clare et al, 1995;Yamamoto et al, 1997;Yamamoto et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pharmacological assays have provided evidence that, after pheromone recognition, the signal transduction pathway in cyprids involves cAMP (Rittschof et al 1986;Clare et al 1995). Also, studies suggest that protein kinase C (PKC) participates in the signal transduction pathway leading to metamorphosis since cyprids treated with PKC activators metamorphosed without prior attachment (Yamamoto et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Larval settlement assays to detect the inducing or inhibiting effect of various substances or substrates on this species have been conducted by several authors (Rittschof et al, 1984(Rittschof et al, , 1992Kon-ya and Miki, 1994;Kitamura et al, 1995;Yamamoto et al, 1995;Satuito et al, 1996;Matsumura et al, 1998 a, b, c;Mishra et al, 1998;Kitamura, 1999;Mishra and Kitamura, 2000). The larval development of both Megabalanus volcano and M. rosa under laboratory conditions has been described (Kado and Hirano, 1994;Okano et al, 1996), but no settlement assay method for these barnacles has yet been reported.…”
mentioning
confidence: 99%